OBJECTIVES AND TASKS OF STRATEGIC LEVEL INTELLIGENCE - Zakirov Qudrat Sunnatovich (Bright Mind Publishing, 2025)
Counterintelligence is also engaged in recruiting foreign citizens on the territory of its own state and can thus obtain information of an intelligence nature, that is, it performs intelligence functions. The article analyzes the goals and tasks of strategic-level intelligence based on open sources.
Keywords: Intelligence, counterintelligence, foreign citizens, intelligence functions, strategic-level intelligence.